ARGUMENTASI MATEMATIK SEBAGAI SEBUAH KOMPETENSI MATEMATIK - Suhendra, Suhendra (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2010)
Teaching and learning mathematics should provide opportunity to student to express, explain, and give reason regarding what they are thinking. In addition, teaching and learning mathematics should make student active, creative, efective, meaningful, and joyful. Students are able to think accurately and communicate properly. These are relevant to the essence of teaching and learning mathematics, mathematical thinking and mathematical communication. By teaching and learning matematics student is supported to catch the idea of concepts, rules, and principles of mathematics, and then revoicing all of them. Even they should be able to defence what they assume as rightness argumentatively (mathematical argumentation or mathematical reasoning). Even though mathematical argumentation is one of important mathematical competences, but it has to make student to proportionaly master. However, mathematical argumentation is mathematical creativity with in tolerances to get the real meaning of learning mathematics. Teaching and learning mathematics can use to (i) highlight ideas that have come directly from students; (ii) help develop students’ understanding that are implicit in those ideas; (iii) negotiate meaning with students, and (iv) add new ideas, or move discussion in another direction.